Intermediaries in the Online Advertising Market - D’Annunzio, Anna; Russo, Antonio (Marketing Science, 2024)
We analyze the ad tech market, investigating an intermediary’s choice to disclose information to advertisers in auctions and publishers’ outsourcing decisions.